ANALISIS KINERJA SEKTOR PUBLIK (PDAM KABUPATEN MEMPAWAH) MENGGUNAKAN ASPEK KEUANGAN DAN NON KEUANGAN - Pratama, Ade Putri (Jurusan Akuntansi, Fakultas Ekonomi dan Bisnis, Universitas Tanjungpura, 2018)
Performance assessment is needed to find out how far the target or results obtained by the company are achieved, and as an ingredient to make improvements or evaluations. In the Minister of Home Affairs Decree No. 47 of 1999 concerning guidelines for evaluating the performance of Regional Water Supply Companies (PDAMs), that indicator in assessing the performance of PDAM performance is seen from three main aspects, namely financial aspects, operational aspects, and administrative aspects. The formulation of the problem in this study is: